What drives land-use change in the United States? A national analysis of landowner decisions - Robert N. Stavins; Ruben N. Lubowski; Andrew J. Plantinga (Fondazione Eni Enrico Mattei (FEEM), 2008)
Land-use changes involve important economic and environmental effects with implications for international trade, global climate change, wildlife, and other policy issues. We use an econometric model to identify factors driving land-use change in the United States between 1982 and 1997. We quantify the effects of net returns to alternative land uses on private landowners' decisions to allocate land among six major uses, drawing on detailed micro-data on land use and land quality that are comprehensive of the contiguous U.S. This analysis provides the first evidence of the relative historical importance of markets and Federal farm policies affecting land-use changes nationally.
Keywords: O51; Q15; 330; Land Use; Land-Use Change; Econometric Analysis; Simulations